2023
DOI: 10.1038/s41586-023-05720-6
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage fumarate hydratase restrains mtRNA-mediated interferon production

Abstract: Springer Nature or its licensor (e.g. a society or other partner) holds exclusive rights to this article under a publishing agreement with the author(s) or other rightsholder(s); author self-archiving of the accepted manuscript version of this article is solely governed by the terms of such publishing agreement and applicable law.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
69
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 70 publications
(89 reference statements)
1
69
0
Order By: Relevance
“…Surprisingly, this was in sharp contrast to fumarate esters, which are successfully used in the management of inflammatory diseases such as psoriasis and multiple sclerosis [36] . In addition, the inhibition of fumarate hydratase suppresses the expression of Il-10 that leads to increased TNFα release [35] . Accumulated citrate, which is exported from the mitochondria to the cytoplasm, is converted to acetyl-coA that is directed towards the production of inflammatory lipid-mediators such as prostaglandins (PGs) [37] (Figure 2, left panel).…”
Section: Immunometabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, this was in sharp contrast to fumarate esters, which are successfully used in the management of inflammatory diseases such as psoriasis and multiple sclerosis [36] . In addition, the inhibition of fumarate hydratase suppresses the expression of Il-10 that leads to increased TNFα release [35] . Accumulated citrate, which is exported from the mitochondria to the cytoplasm, is converted to acetyl-coA that is directed towards the production of inflammatory lipid-mediators such as prostaglandins (PGs) [37] (Figure 2, left panel).…”
Section: Immunometabolismmentioning
confidence: 99%
“…Thus, the concept that metabolic activities dictate the function of immune cells was coined as "immunometabolism" in the early 2010s [41] . Since then, several seminal studies have demonstrated how diverse metabolites function as signaling intermediates that dictate the immune response [10,35,[42][43][44] . Interestingly, it is increasingly being recognized that bacterial pathogens can subvert immunometabolism to promote infection [12,45,46] .…”
Section: Immunometabolismmentioning
confidence: 99%
“…Released mtDNA and mtRNA have been reported to activate cytosolic nucleic acid sensors to induce type-I interferon production and inflammatory response. 3,4 Zecchini et al 1 and Hooftman et al 2 illustrated that FH deficiency induced an IFN response via the release of mtDNA or mtRNA in different physiological models, which is a novel crosstalk between mitochondrial metabolism and innate immunity. The accumulation of fumarate, a key metabolite of the TCA cycle, is likely to play a crucial role.…”
mentioning
confidence: 99%
“…mtDNA was previously reported to be transmitted between tumor cells via extracellular vesicles, 5 but the transport of mtDNA in MDVs was identified for the first time. Hooftman et al 2 found that FH inhibition resulted in the release of mtRNA by increasing the MMP. There are few reports on the mechanism of mtRNA release, mainly the observation of mtRNA release due to the Bcell lymphoma-2 associated X, apoptosis regulator/B-cell lymphoma-2 antagonist/killer 1-mediated permeabilization of the outer membrane during programmed cell death.…”
mentioning
confidence: 99%
See 1 more Smart Citation